Skeletal Muscle Response to Endurance Training in IL-6−/− Mice - Wojewoda, M.; Kmiecik, K.; Majerczak, J.; Ventura-Clapier, R.; Fortin, D.; Onopiuk, M.; Rog, J.; Kaminski, K.; Chlopicki, S.; Zoladz, J. A. (International Journal of Sports Medicine, 2015)
We examined effects of moderate-intensity endurance training on muscle COX/CS activities and V’O2max in control WT and IL-6−/− mice. Animals were exercised for 10 weeks on treadmill for 1 h, 5 days a week at velocity of 6 m·min−1 which was increased by 0.5 m·min−1 every 2 weeks up to 8 m·min−1 . Training triggered an increase of enzyme activities in soleus muscle of WT mice (COX: 480.3±8.9 U·g−1 in sedentary group vs. 773.3±62.6 U·g−1 in trained group, P<0.05 and CS: 374.0±6.0 U·g−1 in sedentary group vs. 534.2±20.5 U·g−1 in trained group, P<0.01, respectively) whereas no changes were observed in soleus of IL6−/− mice. Moreover, in mixed gastrocnemius muscle of trained IL-6−/− mice enzyme activities tended to be lower (COX: 410.7±48.4 U·g−1 for sedentary vs. 277.0±36.5 U·g−1 for trained group and CS: 343.8±24.6 U·g−1 for sedentary vs. 251.7±27.1 U·g−1 for trained group). No changes in V’O2max were observed in WT and IL-6−/− mice after training. Concluding, moderate-velocity endurance training-induced increase in COX and CS activities in muscles of WT mice only which suggests that IL-6 regulates training-induced skeletal muscle responses to exercise.
Keywords: IL-6 knockout; exercise; cytochrome C oxidase activity; citrate synthase activity